(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Diatoms are unicellular, photosynthesizing algae found in fresh and marine waters as well as in moist soil. This research aims to identify different diatoms present in different water bodies in Delhi region. The sample collection for this study was undertaken during January to March 2021 from 14 water bodies which includes eight lakes, three ponds, one river, one canal, and one well. All collected samples of diatoms from were then heat fixed individually and observed under microscope. Diatoms were then identified by analyzing their morphology. In total 117 diatoms, 7 morphological structure and 32 genera were identified. In order to link both the suspect and the victim with crime scene, morphological and genera-based information of Diatoms and their Databank will facilitate to narrow down the selection of water bodies of a particular site. Hence, this research plays a vital role in forensic science as to pen down with information and support in the investigation for drowning site.